(untitled) (Journal of Forest and Livelihood, 2004)
Benefit distribution pattern in community- based resource management have become major issues since few years. Only highlighting successful institutional attributes to manage forest resource may be detrimental in long run. This study explores the value of Non-Timber Forest Products (NTFPs) extracted from the community forestry and their distributional pattern based on wealth categories of households. Findings show that value of NTFPs is higher than other forest products like timber and the gross value of extracted NTFPs is higher in weather household than poor. Households with large land and livestock size gaining more benefit from the community forestry. Some of new rules and regulations in community based resource management tried to exclude poor societies rather than secure them. The recommendation of this study to improve community forest management in Nepal is reformulation of users’ rights to support rural livelihood particularly poor and marginal households.